Medication Adherence, Glycemic Control, and Quality of Life Among Patients with Type 2 Diabetes Mellitus at a Primary Health Center in Makassar, Indonesia - Putri A, Annisa; Suarnianti; Fajriansi, Andi (Indonesian Journal of Nursing and Health Care, 2026)
Background: Diabetes Mellitus is a chronic disease characterized by high blood sugar levels which can affect quality of life, instability of blood sugar levels and compliance with taking medication.Objective: The aim of this study was to determine the relationship between medication adherence and blood sugar levels with quality of life in type II diabetes mellitus patients at the Kassi-Kassi Community Health Center.Methods: This study uses a quantitative research method with a cross-sectional approach. The research location is at the Kassi-Kassi Community Health Center in Makassar City. Sampling used purposive sampling with a population of 190 and a sample of this study amounted to 65 respondents, data collection using the Morisky Medication Adherence Scale-8 questionnaire for medication adherence, the Quality of life-brief clinical inventory questionnaire for quality of life and observation sheets for Random Blood Glucose (RBG)examination. observation sheets and analyzed using the parametric Pearson/non-parametric Spearman rho test.Results: The results of the study showed that there was a relationship between the level of compliance in taking medication and quality of life with a p value of 0.001, there was no relationship between Random Blood Glucose (RBG)and quality of life with a p value of 0.010.Conclusion: The conclusion of this study is that there is a relationship between medication adherence and quality of life, but no relationship between blood sugar levels and quality of life. To lower blood sugar levels in diabetic patients, adherence to medication and maintaining a healthy lifestyle can help maintain a high quality of life.